Electoral Cycles in Savings Bank Lending - Florian Englmaier; Till Stowasser (Center for Economic Studies and ifo Institute (CESifo), 2013)
We provide evidence that German savings banks - where local politicians are by law involved in their management - systematically adjust lending policies in response to local electoral cycles. The different timing of county elections across states and the existence of a control group of cooperative banks - that are very similar to savings banks but lack their political connectedness - allow for clean identification of causal effects of county elections on savings banks' lending. These effects are economically meaningful and robust to various specifications. Moreover, politically induced lending increases in incumbent party entrenchment and in the contestedness of upcoming elections.
Keywords: G21; D72; D73; 330; bank lending cycles; political business cycles; political connectedness; public banks; government ownership of firms